Sales and Collection - MS Access Application: A Comprehensive Reporting and Data Management Solution - Kumar, Rajan (Journal Dekstop Application (JDA), 2025)
This study presents the development of a Sales and Collection System designed on the Microsoft Access platform to enhance financial management efficiency in small and medium-sized enterprises (SMEs). The system integrates relational database principles, SQL-based query processing, and Visual Basic for Applications (VBA) automation to streamline sales transactions, payment tracking, and reporting. Its architecture combines modular design, normalized data structures, and a user-oriented interface that simplifies data handling and supports real-time financial monitoring. Interactive drill-down reports transform static records into analytical insights, enabling managers to evaluate performance and prioritize collection activities effectively. The system demonstrates substantial improvements in workflow efficiency, data accuracy, and decision-making by reducing manual input, minimizing errors, and consolidating financial operations within a single environment. Despite inherent limitations in scalability, platform dependency, and cloud integration, the solution remains a practical and cost-effective option for SMEs with moderate data volumes. Future enhancements may include integration with accounting and e-commerce platforms, web-based accessibility, and mobile extensions to improve flexibility and responsiveness. Overall, the project illustrates how Microsoft Access can serve as a viable foundation for data-driven business management when supported by sound design, structured development practices, and user-centered implementation.